2021
DOI: 10.24272/j.issn.2095-8137.2020.266
|View full text |Cite
|
Sign up to set email alerts
|

Description of a new species of the genus <i>Uropsilus</i> (Eulipotyphla: Talpidae: Uropsilinae) from the Dabie Mountains, Anhui, Eastern China

Abstract: During a terrestrial vertebrate survey of the Dabie Mountains in Anhui Province, eastern China, we collected four Asian shrew mole specimens (hereafter, shrew moles). Based on published literature and comparison with previously collected materials, the four specimens were similar to shrew moles from the mountains of Southwest China; however, no species in this group has been previously recorded from the Dabie Mountains. The genetic and morphological characteristics of the specimens were analyzed, based upon wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 18 publications
1
17
0
Order By: Relevance
“…The distribution of P. latimaxillata unlikely extends eastward or northward as there are no suitable habitats-the species may have a restricted distribution in Dabie Mountains, far apart from the other Asiatic short-tailed shrews. This discontinuous distribution pattern is similar to that of two other new species in the Order Eulipotyphla recently discovered in the Dabie Mountainsthe shrew-like mole Uropsilus dabieshanensis Hu et al, 2021 and the nectogaline shrew Chodsigoa dabieshanensis (Hu et al 2021. Parablarinella latimaxillata is genetically and morphologically distinctive from all the other Asiatic short-tailed shrews.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The distribution of P. latimaxillata unlikely extends eastward or northward as there are no suitable habitats-the species may have a restricted distribution in Dabie Mountains, far apart from the other Asiatic short-tailed shrews. This discontinuous distribution pattern is similar to that of two other new species in the Order Eulipotyphla recently discovered in the Dabie Mountainsthe shrew-like mole Uropsilus dabieshanensis Hu et al, 2021 and the nectogaline shrew Chodsigoa dabieshanensis (Hu et al 2021. Parablarinella latimaxillata is genetically and morphologically distinctive from all the other Asiatic short-tailed shrews.…”
Section: Discussionsupporting
confidence: 85%
“…The divergence of P. latimaxillata and P. griselda appears to have occurred in the Pliocene period, similar to the divergence between U. dabieshanensis and its congeneric species from southwestern and central China (Hu et al 2021). geographic and paleontological evidence has suggested that eastern Asiaincluding the Dabie Mountains-experienced cooling and aridification during this time (Feng 1976;Qiu and Li 2005;ge et al 2013), which triggered the differentiation of mammalian faunas.…”
Section: Discussionmentioning
confidence: 80%
“…Regarding the Chinese shrew mole, on the basis of morphological characteristics and the geographic location, we tentatively assigned the found individual to U. soricipes 5 . Given that recent studies showed that the number of species in the genus Uropsilus may be much larger than is currently known 9 , 22 , we cannot be confident that this individual is a true U. soricipes . In this study, it is referred to as U. aff.…”
Section: Methodsmentioning
confidence: 83%
“…nov., was recently described based on morphological and molecular genetic data 22 ; thus, now the genus is thought to comprise seven species. At least 15 monophyletic lineages of Uropsilus have been recognised using molecular markers, and it seems that the taxonomic diversity of this genus may still be underestimated 9 , 22 . Until now, karyotypes of only two species, U. nivatus and U. andersoni , have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…As the highest-ranking species according to ES, the gracile shrew mole possesses additional features associated with echolocation, such as nocturnal habit, reduced eyes, and large external ears, which further suggests that this species may use echolocation ( 21 ). It is noted that all eight recognized species of shrew moles (subfamily Uropsilinae) share similar ecological and morphological traits ( Fig.…”
Section: Main Textmentioning
confidence: 99%